2021
DOI: 10.1108/sasbe-08-2021-0140
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of solar photovoltaic deployment in South African public universities: a Delphi study

Abstract: PurposeSolar photovoltaic energy is the fastest growing renewable energy in South Africa, and deployment at public universities is critical in order to meet the high energy demand on campuses in a more sustainable manner. To promote and support deployment, it is necessary to know the factors that drive adoption of the technology. Thus, the aim of this study was to identify the factors which engender deployment of photovoltaic energy in public universities in South Africa.Design/methodology/approachThrough an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
0
0
Order By: Relevance
“…The study suggested that the system enables the organisation to identify operational improvements while significantly improving its environmental performance, lowering its annual carbon footprint, and gaining new business. Meanwhile, Geh et al, [46] investigated the factors influencing solar PV deployment in Africa. The findings demonstrated the critical roles of direct and indirect benefits, societal effects, and relative advantage in deploying photovoltaic energy by public universities.…”
Section: Prior Studies Of Solar Pv Adoptionmentioning
confidence: 99%
“…The study suggested that the system enables the organisation to identify operational improvements while significantly improving its environmental performance, lowering its annual carbon footprint, and gaining new business. Meanwhile, Geh et al, [46] investigated the factors influencing solar PV deployment in Africa. The findings demonstrated the critical roles of direct and indirect benefits, societal effects, and relative advantage in deploying photovoltaic energy by public universities.…”
Section: Prior Studies Of Solar Pv Adoptionmentioning
confidence: 99%